THE INTERSECTION OF TECHNOLOGY AND EMPLOYEE EXPERIENCE IN ENHANCING ENGAGEMENT AND SATISFACTION - Hety Devita; Loso Judijanto; Khaeruman; Yeti Rohayati; Henny Noviany (CV. Adiba Aisha Amira, 2025)
This research explores the nexus of technology and employee experience, delving into their combined influence on engagement and satisfaction in the evolving workplace. Rapid technological advancements necessitate reexamining human resources practices, prompting a comprehensive literature review. Key themes include the impact of digital communication tools, the transformative role of wellness apps, ethical considerations in HR technology, and emerging trends. Findings highlight the intricate dynamics shaping the employee experience, stressing the importance of balancing technological integration while preserving the human touch. The implications for practice and policy offer actionable recommendations for organizations, emphasizing cultivating a workplace culture prioritizing employee well-being. This study contributes to understanding how strategically employed technology can optimize engagement and satisfaction, providing insights for organizations navigating the dynamic landscape of the modern workplace.